Design of College Physical Education Curriculum Based on Mobile App Development Platform. (17th June 2022) - Ben, Huanfa; Wang, Li; Ma, Zhaogui; Yang, Junjun
Abstract : As a new term, mobile client app is common in the software market and has mature commercial cases, while for mobile client app of educational content, it is relatively new. The purpose of this paper is to design the sports curriculum app in line with the current university. This paper uses the research method of questionnaire to investigate and analyze the current situation of the organization and management of sports activities and public sports facilities of college students in Taian. Based on the analysis of the influence of sports app on college students' sports behavior, it constructs the theoretical framework of school campus sports management system with app as the carrier. The experimental results show that about 41% of the students in the city use sports app, mainly including running app and fitness app. It can have a significant and positive impact on students' physical activity and sports motivation, but it has no significant effect on students' choice of sports. Through the realization of the physical education teaching function of the campus sports app, students can get rid of the restriction of venue, organization form, and time and make students exercise independently under the guidance of science and system. This design has very important practical significance.